2012
DOI: 10.5012/bkcs.2012.33.5.1561
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Intramolecular Proton Transfer of Alanine Radical Cations

Abstract: The structures of the four lowest alanine conformers, along with their radical cations and the effect of ionization on the intramolecular proton transfer process, are studied using the density functional theory and MP2 method. The energy order of the radical cations of alanine differs from that of the corresponding neutral conformers due to changes in the basicity of the NH2 group upon ionization. Ionization favors the intramolecular proton transfer process, leading to a proton-transferred radical-cation struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Recently, the intramolecular effects that determine amino acid conformational preferences have been replaced under discussion . Traditionally, intramolecular hydrogen bonding (IHB) has been considered sufficient to explain the conformational behavior of amino acids . However, it has been shown that the combination of steric and hyperconjugative effects, and not IHB, determines glycine, alanine, sarcosine and dimethylglycineconformational energies .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the intramolecular effects that determine amino acid conformational preferences have been replaced under discussion . Traditionally, intramolecular hydrogen bonding (IHB) has been considered sufficient to explain the conformational behavior of amino acids . However, it has been shown that the combination of steric and hyperconjugative effects, and not IHB, determines glycine, alanine, sarcosine and dimethylglycineconformational energies .…”
Section: Introductionmentioning
confidence: 99%
“…The characterization of the responsible forces that determine amino acid conformational isomerism is not a simple procedure and requires special attention. However, the peer‐reviewed literature of conformational analysis of amino acid compounds arbitrarily continues to assume that IHB dictates conformational energies . How could arbitrary assumptions concerning the contribution of the intramolecular forces actuating in these conformational complex compounds be justified?…”
Section: Introductionmentioning
confidence: 99%
“…He also examined the utility of self-stabilized anionic species to stabilize amino acid zwitterionic structures. On the basis of this finding, and as continuation of our studies on organic radicals 22,23 and alanine radical cations, 24 we report the effects of halogen anions on the stability of the alanine zwitterion in this paper.…”
Section: 8mentioning
confidence: 56%
“…Another question that requires explanation is whether self-protonation processes occur via hydrogen or proton abstraction. Several theoretical questions regarding the fragmentation of amino acids' cation-radicals [13][14][15][16] and intramolecular proton transfer in amino acids [17][18][19][20] have been examined in the literature. One should note, however, that while mass spectrometrically observed protonated amino acids might be products of intramolecular reactions, these reactions cannot occur in a single amino acid, but rather proceed within their higher mass charged complexes or as an intermolecular particle transfer during two-body collisions between charged and neutral amino acids [5].…”
Section: Introductionmentioning
confidence: 99%